An analysis of expropriation protection mechanism in Bilateral Investment Treaties (BITs) within the context of permanent sovereignty over natural resources - Leonardus J. Gerber (University of Pretoria, 2017)
Mini Dissertation (LLM)--University of Pretoria, 2017.